Implementasi Kebijakan Perwali Surabaya Nomor 17 Tahun 2018 Tentang Penyelenggaraan Hari Bebas Kendaraan Bermotor (Studi Kasus Taman Bungkul Jl. Raya Darmo Surabaya) - Enggar Rahayu Putri (Asketik : Jurnal Agama dan Perubahan Sosial, 2019)
The effects of traffic activities on increasing pollution and human health concentrations have become a concern. In many cities air quality problems are mostly caused by motor vehicle emissions (WHO, 2005) Based on data published by the Central Statistics Agency (BPS) in 2017, the number of motorized vehicles in Indonesia is Â± 129 million in 2016. Surabaya as a city the second largest in East Java with Motor Vehicles as much as Â± 2,126 million Motor Vehicles, making the Regulation of Surabaya City Mayor Number 17 of 2018, Car Free Day where this regulation is a reference in the implementation of Car Free Day in Eight points in Surabaya.In this study, the researcher used the Implementation Theory of Donald S. Van Meter and Carl E. Van Horn. According to Donald S. Van Meter and Carl E. Van Horn. In this study researchers used the six variables as a reference in the process of examining the Implementation Regulation of Surabaya City Mayor Number 17 of 2018, Car Free Day. The researcher used a type of qualitative descriptive research which then carried out Data Collection Techniques with Observation, in-depth interviews, and Documentation that could help to answer all the problems that the researcher made.The results of this study indicate the Implementation Regulation of Surabaya City Mayor Number 17 of 2018, Car Free Day in Bungkul Park Jl. Raya Darmo Surabaya, which is reviewed from 6 Implementation variables to solve the problem are: (1) Standards and Policy Objectives in the field have not been implemented according to the Function and Purpose, (2) Resource Policy is obtained from the City of Surabaya Regional Budget, (3) Inter-Organization Implementation and Communication Activities that have been established in implementing this policy are running well between the Implementation Team in accordance with their respective duties and responsibilities, (4) Characteristics of Implementing Organizations strengthened by the existence of a policy hierarchy formed based on the existing Implementation Team's Decree (5 ) Economic and social conditions that occur in the community are related to economic activities and changes in social activities in the community and (6) Disposition / Attitudes of implementers in the field have been running but not maximally because there is no reference to sanctions to take decisive actions or attitudes. Suggestions from this study are the firmness of the implementing party of the Car Free Day (CFD) program to more deeply disseminate information to the public, issue legal regulations so that anyone who violates can get strict sanctions, provide facilities to support Car Free Day (CFD) activities such as provide adequate Parking and Land for economic activities so as not to interfere with the implementation of this Policy in accordance with the Standards and Policy Objectives.